PRODUCTION OF BIOENERGY USING MICROBIAL FUEL CELL - MAQSOOD, SANA; JABBAR, ZURIAT; MARYAM, HANNANA; ALI, SIKANDER (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
Microbial Fuel Cell (MFC) is an excellent emerging technology for energy generation using a wide variety of substrates including organic and inorganic matter of wastewaters, industrial sludge or renewable biomass. MFC uses microbial catalytic activity to convert biodegradable energy into bioelectric energy. Moreover it is also advantageous in the field of wastewater treatment. The problem with these systems is that energy production is low and not continuous. Researchers have been working from last decade to resolve these problems and to increase energy production. For further improvements, an understanding of microbiology and substrates used in these systems is required. This research review gives a brief account of the commonly used microorganisms in MFC. Different substrates that have been used so far like glucose, acetate, wastewaters, dyes and other inorganic substrates with current density produced by them are also discussed. At the end, applications of MFC are also described.